2022
DOI: 10.1021/acs.nanolett.1c04382
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Tuning of Single-Atom Fe–N–C Catalysts with Phosphorus for Robust Electrochemical CO2 Reduction

Abstract: The electrochemical reduction of CO2 to produce carbon-based fuels and chemicals possesses huge potentials to alleviate current environmental problems. However, it is confronted by great challenges in the design of active electrocatalysts with low overpotentials and high product selectivity. Here we report the atomic tuning of a single-Fe-atom catalyst with phosphorus (Fe–N/P–C) on commercial carbon black as a robust electrocatalyst for CO2 reduction. The Fe–N/P–C catalyst exhibits impressive performance in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(121 citation statements)
references
References 44 publications
4
117
0
Order By: Relevance
“…Chemie cussions, the S-doping in the second shell of FeN 4 boosts the CO 2 electroreduction to CO with regard to the pristine FeN 4 . Notably, the Fe-based SAC usually shows a small current density of CO 2 RR in recent reports [5,22,[49][50][51] due to the sluggish CO 2 RR kinetics. Such an S-doping strategy plays an essential role in improving CO 2 RR kinetics and breaking the limitation of enhancing CO 2 RR performance for Fe-based SAC.…”
Section: Methodsmentioning
confidence: 99%
“…Chemie cussions, the S-doping in the second shell of FeN 4 boosts the CO 2 electroreduction to CO with regard to the pristine FeN 4 . Notably, the Fe-based SAC usually shows a small current density of CO 2 RR in recent reports [5,22,[49][50][51] due to the sluggish CO 2 RR kinetics. Such an S-doping strategy plays an essential role in improving CO 2 RR kinetics and breaking the limitation of enhancing CO 2 RR performance for Fe-based SAC.…”
Section: Methodsmentioning
confidence: 99%
“…The EXAFS spectrum was satisfactorily fitted using the Fe–N backscattering pathway, and the main broad peak at ∼ 1.53 Å in the R space of the FT-EXAFS spectrum could be attributed to the backscattering of Fe–N first-shell coordination. 3 The average coordination number of the N atoms was determined to be 4.1. Therefore, the experimental results confirmed that the SAs were coordinated with four N atoms to generate the Fe–N 4 square-planar configuration.…”
Section: Resultsmentioning
confidence: 99%
“…The signicantly increased consumption of fossil fuels and critical environmental concerns have encouraged the pursuit of environment-friendly and renewable energy technologies. [1][2][3][4][5] Fuel cells and metal-air batteries with the merits of low emission, high energy density and superior energy conversion efficiency support pivotal approaches to clean energy challenges. [6][7][8][9][10][11][12][13] An essential step that signicantly limits the performance of these devices is the cathodic oxygen reduction reaction (ORR), which depends heavily on the electrocatalysts containing platinum group metals (PGMs).…”
Section: Introductionmentioning
confidence: 99%
“…cussions, the S-doping in the second shell of FeN 4 boosts the CO 2 electroreduction to CO with regard to the pristine FeN 4 . Notably, the Fe-based SAC usually shows a small current density of CO 2 RR in recent reports [5,22,[49][50][51] due to the sluggish CO 2 RR kinetics. Such an S-doping strategy plays an essential role in improving CO 2 RR kinetics and breaking the limitation of enhancing CO 2 RR performance for Fe-based SAC.…”
Section: Forschungsartikelmentioning
confidence: 99%